2022
DOI: 10.3390/cancers14225619
|View full text |Cite
|
Sign up to set email alerts
|

BMN673 Is a PARP Inhibitor with Unique Radiosensitizing Properties: Mechanisms and Potential in Radiation Therapy

Abstract: BMN673 is a relatively new PARP inhibitor (PARPi) that exhibits superior efficacy in vitro compared to olaparib and other clinically relevant PARPi. BMN673, similar to most clinical PARPi, inhibits the catalytic activities of PARP-1 and PARP-2 and shows impressive anticancer potential as monotherapy in several pre-clinical and clinical studies. Tumor resistance to PARPi poses a significant challenge in the clinic. Thus, combining PARPi with other treatment modalities, such as radiotherapy (RT), is being active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 166 publications
0
2
0
Order By: Relevance
“…The function of HR proteins in DNA replication and the accumulation of persistent ssDNA gaps in HR-deficient tumors have been linked to PARP inhibitor sensitivity and platinum compounds-induced cell killing [192]. Various aspects of PARPi sensitivity and acquired resistance in cancer therapy are reviewed elsewhere [193][194][195].…”
Section: Exploiting Weaknesses Of Dsb Processing To Improve Radiation...mentioning
confidence: 99%
“…The function of HR proteins in DNA replication and the accumulation of persistent ssDNA gaps in HR-deficient tumors have been linked to PARP inhibitor sensitivity and platinum compounds-induced cell killing [192]. Various aspects of PARPi sensitivity and acquired resistance in cancer therapy are reviewed elsewhere [193][194][195].…”
Section: Exploiting Weaknesses Of Dsb Processing To Improve Radiation...mentioning
confidence: 99%
“…Internal irradiation radiotherapy can be precisely targeted to tumor tissues to exert drug effects, but fewer studies in this area have been reported so far, which deserves more in-depth exploration. To date, dozens of clinical trials combining PARP inhibitors with radiotherapy are registered, which mainly involve testing of veliparib or olaparib ( Table 2 ) ( 119 ).…”
Section: Advances In Parp1 and Its Inhibitorsmentioning
confidence: 99%